Religion and Social Interaction (Case Study of Relationship between Spiritual Activists and Spiritual Activists with Adherents of Other Religions at SMAN 79 South Jakarta) - Syarifah Alawiyah (Trigin Publisher, 2021)
Religion cannot be separated from the life of its adherents. Religion can be related to social stratification, social solidarity, and sometimes religion is associated with social conflicts that have occurred in several areas in Indonesia Religion cannot be separated from the social interactions of its adherents, because religion is a way of life which they serve as the main reference in behave, speak and act. Every religious teaching – any religion – will lead its adherents to build a harmonious relationship with fellow believers and followers of other religions, therefore every religious adherent always tries to establish a relationship with his environment as best as possible. In this study, the author issues problems in the relationship between religion and social interaction, in this case the relationship between followers of one religion and other religions.